Legal Protection and Tax Treaty Position for Taxpayer Against Double Taxation Based on Legislation Regulations - Sahrawati Sahrawati; Ardiansyah Ardiansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to obtain information and legal analysis regarding legal protection and the position of the tax treaty against double taxpayers (Double Taxation), double taxation is the imposition of taxes on the same type of tax by different countries on the same subject and object, and in identical periods. The birth of double taxation is due to the principle of global taxation for domestic taxpayers, where income from within the country and abroad is taxed by the resident country (the country of residence of the taxpayer), besides that there is also territorial taxation for foreign taxpayers by the source country. where income originating from that country is taxed by the source country. To avoid state losses, a tax treaty was born which is part of international law, which minimizes double taxation and attempts to avoid tax.